The role of the state in health public policies: an overview of the debate on the concept of State and the Brazilian case - Pessoto, Umberto Catarino; Werneck Ribeiro, Eduardo Augusto; Guimaraes, Raul Borges [UNESP] (Univ Sao Paulo, Fac Saude Publica, 2015)
This article is the result of a narrative literature review. The objective is to show the development of an overview on the ideological debate on the design of state health policies. We argue that the role of the state in the development of health policy, even under the pressure of the global market, may create alternatives to promote and drive economic and social development, meaning they are not subject to economic constraints imposed by the liberal ideal of market. Here is a part of a theoretical discussion about the construction and presence of the State in Latin America, particularly in Brazil. We take the approaches of the Marxist tradition and liberal to the issue as reference. This discussion allows us to understand the historical role of the state in the maintenance of social policies, specifically health, is an alternative to public control eases the intense capital mobility promoted by economic globalization. In this sense, the theme makes the Brazilian health an important issue of social sciences, why is the historicity of the construction of the Brazilian health system, as a public policy that can mirror the actual reconstruction of the institutional framework of the Brazilian state with the establishment instances of negotiation between the various spheres of power that strengthen the state in this process of democratization of Brazilian society.

Este artigo é resultado de uma revisão bibliográfica narrativa, visando o desenvolvimento de um panorama acerca do debate ideológico sobre a concepção de Estado nas políticas de saúde. Nele, argumentamos que o papel do Estado brasileiro no desenvolvimento da política de saúde, mesmo sob a pressão do mercado globalizado, pode criar alternativas para promover e direcionar o desenvolvimento econômico e social, e que isso não significa submeter-se às restrições econômicas impostas pelo ideal liberal de mercado. Apresentamos parte de uma discussão teórica acerca da construção e presença do Estado na América Latina e, particularmente, no Brasil, tomando como referências as abordagens da tradição marxista e da liberal sobre a questão. Essa discussão permite-nos entender que o papel histórico do Estado na manutenção de políticas públicas sociais, especificamente as de saúde, é uma alternativa para que o controle público amenize a intensa mobilidade de capital promovida pela globalização econômica. Nesse sentido, o tema torna a saúde nacional uma questão importante das Ciências Sociais, por que é na historicidade da construção do sistema de saúde brasileiro, como política pública, que se pode espelhar a própria reconstrução do arcabouço institucional do Estado brasileiro, com a instauração de instâncias de negociação entre as diversas esferas de poder que fortalecem esse mesmo Estado no processo de redemocratização da sociedade brasileira.
Keywords: State; Public health policy; Policy innovation; Public management